KEPUASAN SISWA DALAM MENGIKUTI LAYANAN KONSELING INDIVIDUAL DI SEKOLAH MENENGAH PERTAMA (SMP) NEGERI 1 V KOTO KAMPUNG DALAM - Suci Yandhini; Dodi Pasilaputra; Alfi Rahmi; Hidayani Syam (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the importance of individual counseling services in helping students overcome personal, social, and academic problems. The quality of services provided by school counselors is one of the main factors influencing students' satisfaction with counseling services. This study aimed to describe students' satisfaction with individual counseling services at SMP Negeri 1 V Koto Kampung Dalam. A qualitative descriptive approach was employed. The participants consisted of four students as key informants, along with the counseling coordinator, a school counselor, and the vice principal for student affairs as supporting informants, selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation, then analyzed using data reduction, data display, and conclusion drawing. Data credibility was ensured through source triangulation. The findings indicate that, in general, students were satisfied with the individual counseling services they received. Their satisfaction was reflected in the counselors' reliability, responsiveness, empathy, and ability to create a safe and comfortable counseling environment. The counseling services also helped students better understand themselves, reduce emotional burdens, and make more appropriate decisions in dealing with their problems. However, the positive changes experienced by students were not always sustained over time, indicating the need for continuous follow-up and regular evaluation to improve the effectiveness of individual counseling services in schools